The indigenous languages influence in festive register of the chilean newspaper La Cuarta - San Martín Nuñez, Abelardo (Boletín de Filología, 2009)
The aim of this study is to determine, qualitatively and quantitatively, the nature and extent of lexical borrowing from indigenous languages, as refl ected in a representative sample of a festive register Chilean newspaper, La Cuarta. For this purpose, lexical items from that origin employed with festive intentionality in a corpus of 375 pages of that newspaper were gathered. These lexical items were used to assess the relative vitality of words of Indian origin documented in the corpus (measured by their frequency of occurrence, their capacity to originate derivatives in the host language, their capacity to originate lexical families, and their value in the semantic fi elds that they share with synonymous indigenous borrowings documented in the corpus) and etymological origin (in this respect, the lexicogenetic process undergone by indigenous borrowings to convey their festive connotations). As a result, 132 lexical items of that origin and their derivatives were documented in the corpus. The last section of the article consists of a lexicographic inventory of the Indian loanwords documented and their Spanish derivatives.